Osteotropic Therapy via Targeted Layer‐by‐Layer Nanoparticles. Issue 6 (9th October 2013) - Morton, Stephen W.; Shah, Nisarg J.; Quadir, Mohiuddin A.; Deng, Zhou J.; Poon, Zhiyong; Hammond, Paula T.
<x xml:space="preserve">Abstract</x> Current treatment options for debilitating bone diseases such as osteosarcoma, osteoporosis, and bone metastatic cancer are suboptimal and have low efficacy. New treatment options for these pathologies require targeted therapy that maximizes exposure to the diseased tissue and minimizes off‐target side effects. This work investigates an approach for generating functional and targeted drug carriers specifically for treating primary osteosarcoma, a disease in which recurrence is common and the cure rate has remained around 20%. This approach utilizes the modularity of Layer‐by‐Layer (LbL) assembly to generate tissue‐specific drug carriers for systemic administration. This is accomplished via surface modification of drug‐loaded nanoparticles with an aqueous polyelectrolyte, poly(acrylic acid) (PAA), side‐chain functionalized with alendronate, a potent clinically used bisphosphonate. Nanoparticles coated with PAA‐alendronate are observed to bind and internalize rapidly in human osteosarcoma 143B cells. Encapsulation of doxorubicin, a front‐line chemotherapeutic, in an LbL‐targeted liposome demonstrates potent toxicity in vitro. Active targeting of 143B xenografts in NCR nude mice with the LbL‐targeted doxorubicin liposomes promotes enhanced, prolonged tumor accumulation and significantly improved efficacy. This report represents a tunable approach towards the synthesis of drug carriers, in which LbL enables surface modification of nanoparticles for tissue‐specific targeting and treatment.